1992
DOI: 10.1192/bjp.160.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Cyproterone acetate therapy and aggression

Abstract: CORRESPONDENCE age = 41 .6 (10. 1) years), and eight men (mean (s.d.) age = 46.3 (9.4) years). Three women were divorced and the other eight married, contrasting with twoSCHMIDT, C., KLEE,L. & AMES.G. (1990) Review and analysis of literatures on indicators of women's drinking problems. British JournalofAddiction. 85, 179-192.married men, one separated man and four single, i.e.never married, men, among the seven for whom thisdata was recorded.The mean (s.d.) age of the onset of drinking was21 .8 (7.6) years for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cyproterone acetate (CPA) inhibits the interaction between endogenous androgens and androgen receptors, as well as reducing the biosynthesis of androgens. Effective treatment of ISB with CPA 50 mg was reported in a 60-year-old man with AIDS-related dementia [ 87 ]; however, another case report described unsuccessful CPA treatment in a 70-year-old with dementia, with additional numerous adverse effects impacting on mobility [ 88 ]. CPA 10 mg was used with beneficial effect in two males with dementia-related ISB that had not responded to treatment with antipsychotic or sedative medication.…”
Section: Resultsmentioning
confidence: 99%
“…Cyproterone acetate (CPA) inhibits the interaction between endogenous androgens and androgen receptors, as well as reducing the biosynthesis of androgens. Effective treatment of ISB with CPA 50 mg was reported in a 60-year-old man with AIDS-related dementia [ 87 ]; however, another case report described unsuccessful CPA treatment in a 70-year-old with dementia, with additional numerous adverse effects impacting on mobility [ 88 ]. CPA 10 mg was used with beneficial effect in two males with dementia-related ISB that had not responded to treatment with antipsychotic or sedative medication.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, PPG was used. In most cases, paraphilic sexual behavior disappeared within 2 weeks except for one case; in this latter case, CPA was withdrawn after 2 weeks due to side effects (Byrne et al, 1992). Cooper et al (1992a) reported a better efficacy with 200 mg/day of CPA as compared with 100 mg/day.…”
Section: ✓ Studiesmentioning
confidence: 92%
“…• Case reports Twenty-one patients were reported in 11 case reports (Cooper et al, 1972;Lederer, 1974;Bradford and Pawlack 1987;Grinshpoon et al, 1991;Thibaut et al, 1991 andByrne et al, 1992;Cooper et al, 1992a;Eriksson and Eriksson 1998;Gooren et al, 2001;Panesar et al, 2011, no information available;Amelung et al, 2012 no information provided on the type of antiandrogen therapy in 6 pedophiles). Two pedophilic subjects with mild to moderate mental retardation, one exhibitionist, other non-specified sex offenders (aged from 23 to 70 years, in 2 cases dementia was associated with sexual disinhibition) were receiving CPA (50 to 200 mg/day or 275 to 300 mg i.m.…”
Section: ✓ Studiesmentioning
confidence: 99%
See 1 more Smart Citation